1994
DOI: 10.1111/j.1476-5381.1994.tb17073.x
|View full text |Cite
|
Sign up to set email alerts
|

Role of endogenous endothelin in myocardial and coronary endothelial injury after ischaemia and reperfusion in rats: studies with bosentan, a mixed ETA‐ETB antagonist

Abstract: 1Previous studies suggested that endothelin-l (ET-1) may play a role in myocardial ischaemia and reperfusion. This study was designed to test the effect of a new nonpeptide antagonist of endothelin ETA and ETB receptors, bosentan, on myocardial infarct size, ventricular arrhythmias, and coronary endothelial dysfunction after ischaemia and reperfusion. 2 Anaesthetized male Wistar rats were subjected to 20 min ischaemia (left coronary artery occlusion) followed by 1 h (for the evaluation of coronary endothelial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
21
0
1

Year Published

1996
1996
2011
2011

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(23 citation statements)
references
References 53 publications
(49 reference statements)
1
21
0
1
Order By: Relevance
“…This was similar to that reported for bosentan in human smooth muscle (ETA) and human placenta (ETB): Ki of 4.7 nM and 95 nM, respectively (Clozel et al, 1994). Although oral administration of bosentan decreased mean arterial blood pressure in a conscious rat coronary heart failure model (Teerlink et al, 1994), and reduced elevated blood pressure, vascular hypertrophy and remodelling in DOCA-salt (deoxycorticosterone acetate-salt) hypertensive rats (Li et al, 1994), bosentan did not affect myocyte or coronary endothelial injury in a rat model of ischaemia and reperfusion (Richard et al, 1994). We have previously characterized the mRNA encoding the ET receptors present in human left ventricle using molecular biology techniques .…”
Section: Discussionmentioning
confidence: 99%
“…This was similar to that reported for bosentan in human smooth muscle (ETA) and human placenta (ETB): Ki of 4.7 nM and 95 nM, respectively (Clozel et al, 1994). Although oral administration of bosentan decreased mean arterial blood pressure in a conscious rat coronary heart failure model (Teerlink et al, 1994), and reduced elevated blood pressure, vascular hypertrophy and remodelling in DOCA-salt (deoxycorticosterone acetate-salt) hypertensive rats (Li et al, 1994), bosentan did not affect myocyte or coronary endothelial injury in a rat model of ischaemia and reperfusion (Richard et al, 1994). We have previously characterized the mRNA encoding the ET receptors present in human left ventricle using molecular biology techniques .…”
Section: Discussionmentioning
confidence: 99%
“…Few studies have shown a positive influence of IPC on restoration of cardiac contractile function (49). Protection against vascular dysfunction by IPC also remains controversial (50)(51)(52)(53), but several studies have shown that preconditioning pretreatment protects blood vessels and possibly the microcirculation against vascular stunning (54,55). The mechanisms that are responsible for cytoprotection against infarction and contractile or vascular stunning are not the same, and many of these mechanisms are believed to be shared.…”
Section: Myocardial Protectionmentioning
confidence: 99%
“…In deoxycorticosterone acetate salt-hypertensive rats, ET-1 is a determinant of hypertension. 26,29 Angiotensin II-induced hypertension 30 as well as the hypertension due to the chronic inhibition of NO synthesis 31 is counteracted by the blockade of ET A receptors. Nevertheless, no study has yet clearly determined the consequences of a chronic increase in ET-1 on vascular reactivity.…”
mentioning
confidence: 99%